The therapeutic mechanism of PuRenDan for the treatment of diabetic nephropathy: Network pharmacology and experimental verification. (15th July 2022) - Niu, Hongjuan; Fan, Lu; Zhao, Linyi; Yao, Rongfei; He, Xu; Lu, Binan; Pang, Zongran
Abstract: Ethnopharmacological relevance: Purendan (PRD), as a Chinese medicinal formula, behaves remarkable therapeutic effects on diabetes and complications in clinical and experimental research. However, the underlying pharmacological mechanism in the treatment of diabetic nephropathy (DN) is still unclear. Aims: To investigate the therapeutical effects of PRD on DN and to explore its pharmacological mechanisms using network pharmacology and experimental verification. Materials and methods: The active compounds and putative targets in PRD, and disease-related targets of DN were extracted from public databases. The key targets were identified through the protein-protein interaction (PPI) network and module analysis. The GO and KEGG enrichment analysis were performed to discover potential pharmacological mechanisms. The expression of the key targets was detected in kidney tissue in Gene Expression Omnibus (GEO) dataset. The affinity between key proteins and corresponding compounds was evaluated by molecular docking and validated by the surface plasmon resonance (SPR) assay. The indicators on major pathways and hub genes were verified by in vivo experiments. Results: In network pharmacology, 137 common targets in PRD for DN treatment were screened. The key targets and main signaling pathways including AGE-RAGE and lipid pathways were identified. The statistical difference in the expression of the key targets was verified in GSE96804 database, confirming the association with DN. The docking scores obtained from molecular docking illustrated good binding force between hub proteins and active compounds. And the good component-protein affinities were validated by SPR assay. Furthermore, the results of animal experiment indicated that PRD could ameliorate the level of serum glucose and renal function in rat model. It could regulate the expression of hub targets (AKT1, MAPK3, and STAT3) and improve indicators related with oxidative stress and lipid metabolism. Conclusion: The key targets and major signaling pathways in the treatment of PRD on DN were identified. The mechanism might relate to regulation of oxidative stress and lipid metabolism. Graphical abstract: Image 1 Highlights: The first network pharmacology analysis of PRD in the treatment of DN. The hub genes, including AKT1, STAT3, and MAPK3, are screened and verified in PRD for the treatment of DN. The pharmacological effects of PRD involve AGE-RAGE and lipid signaling pathways.